Methodology for assessing the level of development of closed administrative-territorial units - Shagimuratova A.A.; Makarova A.E.; Sokolnikova A.A.; Konakova K.P. (E3S Web of Conferences, 2023)
The article proposes a new approach to assessing the level of development of closed administrative and territorial units (hereinafter, CATU) to form a favorable and comfortable living environment for people by implementing measures to develop scientific and production, socioeconomic and recreational potential of the territory and infrastructure of the municipality. The criteria and parameters for assessing the level of development of the territory, which ensure sustainable development of the territory, have been identified. A project experiment on the example of the territory of Levin town settlement (former CATU Kirov-200) of Kirov oblast is made. The article deals with the creation of the conceptual project “Biopolis” using the Ishikawa diagram. “Biopolis” is a biopharmaceutical cluster, and the principles of bionics have been applied for the development of the masterplanning scheme. The article proposes a new approach to assessing the level of development of CATUs, which is due to the priority task under the program “Integrated development of single-industry towns”.